Assessment of Peste Des Petits Ruminants (PPR) in Turkey Between 2017-2019 - Bayir, T; Gürcan, İS (Journal of the Hellenic Veterinary Medical Society, 2023)
Peste des petits ruminants (PPR) is a viral disease affecting small ruminants and causes significant agricultural damage. The World Organization for Animal Health (OIE) has classified PPR as an animal disease that must be reported immediately. In this study was aimed to understand of spatial and seasonal epidemiology of PPR in Turkey and provide information by using Geographical Information Systems (GIS). Descriptive and analytical statistics were used in the study, logistic regression analysis was applied to assess the effect of season and species factors on PPR outbreaks occurring in Turkey. Data were obtained from the World Animal Health Information System (WAHIS) database of OIE. Between 2017-2019, 337 outbreaks, 18.467 cases and 11.526 deaths were reported 57 provinces of Turkey and the highest number of PPR outbreaks, cases and deaths were reported in The Central Anatolia Region. On time-wise examination, the PPR risk-areas revealed changes with different levels of endemicity. The Central Anatolia Region were the top outbreaks reported region during 2017-2018, whereas The Marmara Region reported more outbreaks during 2019. PPR outbreaks occurred throughout the year in all seasons, but were most frequently encountered during the winter season (December to February) and the results showed that seasonal and species factors are important in the spread of the disease. PPR has widely distributed throughout the country, and the epidemiological picture suggests that the disease has become an endemic infection in the country. The spatial and seasonal distribution of PPR in Turkey gives useful information on hotspot areas, allowing managers to make informed decisions about prevention and control in different parts of the country. In accordance with the PPR Global Control and Eradication Strategy, the study also outlines when and where extensive surveillance, vaccination, and biosecurity measures are required for the control and eradication of the disease in Turkey.